Comparison of two commonly used clinical cognitive screening tests to diagnose mild cognitive impairment in heart failure with the golden standard European Consortium Criteria. (1st February 2017) - Alagiakrishnan, Kannayiram; Mah, Darren; Dyck, Jason R.B.; Senthilselvan, Ambikaipakan; Ezekowitz, Justin
Abstract: Introduction: This study on mild cognitive impairment (MCI) in heart failure (HF) compares the utility of Montreal Cognitive Assessment (MoCA) to the Mini-Mental Status Exam (MMSE) for diagnosing MCI in a HF population when compared to the golden standard European Consortium Criteria (ECC). Methods: Participants were recruited from the Alberta HEART study at the Mazankowski Alberta Heart Institute in Edmonton and St. Mary's hospital in Camrose. This study enrolled 53 community adults aged > 50 years: 33 HF and 20 controls. Participants were assessed using both the MMSE and MoCA for MCI. MCI was diagnosed using the golden standard, European Consortium Criteria. Sensitivity and specificity analysis, positive and negative predictive values, likelihood ratios and kappa statistic were calculated. Results: The mean age was 72.8 years (SD 8.4), 60.4% were females and 34% had underlying ischemic heart disease. Overall, two thirds of patients (22/33, 66%) with HF had MCI. In comparison to European Consortium Criteria, the sensitivity and specificity of MoCA were 82% and 91% in identifying individuals with MCI, and MMSE were 9% and 91%, respectively. The positive and negative predictive values for MoCA were 95% and 71%, and for MMSE were 67% and 33%, respectively. Kappa statistics showed good agreement between MoCA and consortium criteria (kappa = 0.68) and a low agreement between MMSE and consortium criteria (kappa = 0.07). Conclusion: Cognitive dysfunction is common in patients with HF. Overall, the MoCA seems to be a better screening tool than MMSE for MCI in HF patients.